The impact of coach gender on team performance: A quantitative analysis of women's five-a-side basketball leagues - Kulaijiang, Palizha (Tanjungpura Journal of Coaching Research, 2025)
Background and Study Aim. As women's participation in professional sports continues to grow, the presence and impact of female coaches have attracted increasing scholarly attention. Despite this, empirical evidence regarding the effect of coach gender on team performance remains inconclusive. This study aims to examine the causal impact of head coach gender on team performance in women"™s professional five-a-side basketball leagues, while also investigating the moderating effect of managerial discretion. Material and Methods. This quantitative study utilized a dataset comprising 406 team-season observations from the Women's National Basketball Association (WNBA) and Women's Chinese Basketball Association (WCBA) spanning 1997 to 2024. Team performance was assessed using the TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) method. A weighted least squares (WLS) regression model was employed to estimate the impact of coach gender, while managerial discretion was proxied using coach firing records. Control variables included coach age, professional experience, education level, and tenure. Results. The analysis revealed that female head coaches significantly enhanced team performance, supporting the first hypothesis. However, this positive effect was weakened under conditions of high managerial discretion, supporting the second hypothesis. Additionally, older coaches were positively associated with team outcomes, whereas professional experience, education level, and tenure exhibited negative associations. Conclusions. The findings underscore the complex dynamics of gender in coaching effectiveness and highlight the importance of equitable promotion practices within professional sports organizations. Limitations include the relatively low statistical significance of some variables and the absence of mediating factors. Future research should consider integrating player- and club-level data to provide a more comprehensive understanding.